Design and Characterization of a Cyclic Stress Imposed Accelerated Aging Test Method – Assessment on Tyre Tread Compound - N, Pradeep kumar; Neethirajan, Jeevanandham; Ramanujam, Rajesh Babu; R, Rajendran (International Research Journal of Multidisciplinary Technovation, 2026)
Surface mobility has been one of the greatest enablers of human development, and tyres have played a pivotal role in this journey. The tyre is the only link between the vehicle and the road to enable safety. As a major requirement, the traction is achieved by the tyre with the help of several components of its structure. The tread patterns provide physical interlocking with road asperities and the tread compound interfaces with road textures, to effect necessary grip in dynamic conditions. As the properties of tread compound play the most vital role in affecting dynamic grip, the aging of the rubber and consequent loss of properties have become key topics to study in tyre design for safety and durability assessment. Tread ageing is affected by multiple simultaneous conditions experienced by the tyre, related to thermo-oxidative exposure and mechanical stress variations. While aging is a critical influencer in tread performance preservation, the studies related to aging have made many assumptions due to difficulties in replicating actual service conditions in the laboratory. Traditionally, aging studies were conducted by inducing a thermo-oxidative environment at an elevated temperature above ambient temperature and mapping property degradation as a function of time. This generic approach was fraught with many limitations due to its inability to replicate the degradation characteristics as they happen in real service conditions. A novel attempt is made to develop a facility that simulates real-life service conditions to a greater extent by imposing a cyclic mechanical stress during the accelerated aging process. This study investigates the effect of aging on Natural Rubber (NR) based tyre tread compound under conditions dominant in dynamic service conditions. Unlike conventional accelerated aging without mechanical stimuli (may be called static aging), the current study involves cyclical mechanical stress imposed on the tread compound under elevated temperatures (dynamic aging) to mimic the effect on tyre tread in service conditions. This paper addresses the synergistic interactions mechanical behaviour of tread rubber compound and its microstructure alterations when exposed to static and dynamic aging processes. Various methods in mechanical and viscoelastic studies to verify representative parameters of rubber compound behaviour, such as hysteresis ratio, Mullins coefficient, stress relaxation, and macromolecular network alteration, are introduced. A macromolecular network-alteration mechanism, linking changes in crosslink density and chain scission to the mode and state of aging, is established. The findings significantly reinforce the understanding of compound behaviour alterations with more realistic operating conditions of aging to support the design of materials to enhance product safety.